Genotoxic Potential and Physicochemical Parameters of Sinos River, Southern Brazil - Madalena C. S. Scalon; Ciliana Rechenmacher; Anna Maria Siebel; Michele L. Kayser; Manoela T. Rodrigues; Sharbel W. Maluf; Marco Antonio S. Rodrigues; Luciano Basso da Silva (The Scientific World Journal)
The present study aimed to evaluate the physicochemical parameters and the genotoxic potential of water samples collected in the upper, middle, and lower courses of the Sinos River, southern Brazil. The comet assay was performed in the peripheral blood of fish Hyphessobrycon luetkenii exposed under laboratory conditions to water samples collected in summer and winter in three sampling sites of Sinos River. Water quality analysis demonstrated values above those described in Brazilian legislation in Parobé and Sapucaia do Sul sites, located in the middle and in the lower courses of the Sinos River, respectively. The Caraá site, located in the upper river reach, presented all the physicochemical parameters in accordance with the allowed limits in both sampling periods. Comet assay in fish revealed genotoxicity in water samples collected in the middle course site in summer and in the three sites in winter when compared to control group. Thus, the physicochemical parameters indicated that the water quality of the upper course complies with the limits set by the national guidelines, and the ecotoxicological assessment, however, indicated the presence of genotoxic agents. The present study highlights the importance of combining water physicochemical analysis and bioassays to river monitoring.